STAVOVI I MIŠLJENJA UČENIKA PREMA FIZIČKOM VASPITANJU - Branislav Dragić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Research on positions and opinions which schoolboys and schoolgirls have about the classes of physical education held in two primary schools, "Vozd Karadorde" School and "Kole Rasic" School, where the first one is a central and the second one is a peripheral school in Nis, is based upon a convenient sample of two hundred and ninety students of the sixth grade. After applying the survey technique the results which were gathered contained information about the investigation of positions and opinions about fourteen questionsitems and about the fifteenth one which referred to the basic motives for participation in physical education classes. Both Leakart's three - level scale and Yes, I don't know, No...answers were used. The total number of points won by the students who were questioned represents the final SKORE. Not only the calculations of frequency of the given answers were made, but also percentages and cumulative percentages, arithmetic middle of the chosen students (boys and girls from both schools), and with the help of ANOVA analysis some statistic significance about the difference in arithmetic middles between the scores of the groups of schoolboys and schoolgirls from both schools and the groups inside each of these schools taken separately, was established and the final frequency of the answers was based upon the strata of points and illustrated graphically with a graph chart. Both positive and negative students' positions and opinions about physical education in both schools were ascertained because the obtained average results of scores won by students during the survey were greater than the average values span on a scale of possible answers, and were even moved on the right, in a position so that they entered a zone of better results. Establishing a coefficient of statistical significance of the difference in arithmetic middle between the scores of the groups of schoolboys and schoolboys and schoolgirls of both schools as well as the groups of schoolboys and schoolgirls in each school taken separately, a perceived level of importance was not obtained so that it can beconcluded that the differences in opinions of view do not exist. The most frequent motives for participation in physical education classes in both schools, between boys and girls, are not different. However, it can be noticed that on the one hand the participation in sport activities in the central school is dominant in students' answers while on the other hand games and fun activities are dominant in the answers of students from the peripheral school. The results obtained by this investigation, that is the existence of positive opinion about physical education, encourage us to continue our work in this social sphere and to fulfill the highest goal of physical education classes and that is to form the lasting habit of taking part in physical exercises